Ruth's conversion and the completion of Naomi's journey home : its impact on God's universal mission and redemption - Balitog, Mary Muriel T. (Mary Muriel Ticobay) ([Quezon City, Phils.] : St. Andrew's Theological Seminary, 2014)
By and large, the story of Ruth portrays that even the least expected people, being a descendant of Israel's enemy and with the lowest profile personality in the society, can become a heroine accepted, loved and praised by those around her. That a victorious and famous kings like David and Solomon descended from Moabite converted to Judaism throw light to the understanding that Ruth is the paradigm shift of the righteous convert. It also implies as it inform that anyone seeking affiliation or conversion must take effort to deserve a Ruth-like acceptance in the community or people of God.
As Gunn and Fewell pointed out, the book of Ruth is not only a portrayal of a simple life story to trace the genealogy of David, but it also allows the image of God to be constructed from the beliefs of the characters that were expressed in different and also conflicting points of view
In partial fulfillment of the requirement for the Degree of Masters in Divinity
A thesis presented to the Faculty of St. Andrew's Theological Seminary